Association between chronic disease multimorbidity and leisure-time physical activity: Evidence from the China Multiethnic Cohort study - Li, Yajie; Li, Xianzhi; Yu, Bin; Li, Jingzhong; He, Ruifeng; Nima, Qucuo; Zhou, Junmin (Frontiers in Medicine, 2022)
Objective To reveal the associations between multimorbidity and leisure-time physical activity (LTPA) by ethnicities in China. Materials and methods Self-reported information on a range of occupational, household, transport, and LTPA was collected by interviewer-administered questionnaire. A total of 17 chronic diseases were assessed based on self-reported lifetime diagnoses or medical examinations. Multivariable logistic regression models were used to assess the associations between multimorbidity and the risks of low LTPA. Results The mean age of all participants was 51.2 years old. Of all, 61.4% were women and 57.9% were from the Han population. A significantly negative association (OR = 0.92, 95% CI = 0.89–0.95) was found between multimorbidity and low LTPA, with a stronger association among minority populations (OR = 0.86, 95% CI = 0.82–0.91) than among the Han population (OR = 0.96, 95% CI = 0.92–1.01). For both the minority population and the Han population, digestive system multimorbidity and digestive-metabolic system multimorbidity had a significantly negative association with low LTPA. For the Han population, the association of intersystem multimorbidity for the circulatory-respiratory system (OR = 1.17, 95% CI = 1.04–1.31) with low LTPA was stronger than that of intrasystem multimorbidity for the circulatory (OR = 1.12, 95% CI = 1.01–1.25) and respiratory systems (OR = 1.14, 95% CI = 1.04–1.25). Conclusion There are significant associations between multimorbidity and low LTPA based on this large multiethnic population. Our findings suggest that LTPA-tailored interventions should be designed for specific ethnic groups according to different types of multimorbidity.